2018
DOI: 10.1136/neurintsurg-2014-011125.rep
|View full text |Cite
|
Sign up to set email alerts
|

ADAPT FAST study: a direct aspiration first pass technique for acute stroke thrombectomy

Abstract: Background The development of new revascularization devices has improved recanalization rates and time, but not clinical outcomes. We report a prospectively collected clinical experience with a new technique utilizing a direct aspiration first pass technique with large bore aspiration catheter as the primary method for vessel recanalization. Methods 98 prospectively identified acute ischemic stroke patients with 100 occluded large cerebral vessels at six institutions were included in the study. The ADAPT techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(89 citation statements)
references
References 23 publications
4
84
0
1
Order By: Relevance
“…Further experiments will help to validate and confirm the recalcitrance of our bifurcation model. This includes the evaluation of different established modalities for thrombectomy, such as the ADAPT (A Direct Aspiration First Pass Technique) 17 and ARTS (Aspiration-Retriever Technique for Stroke) 12 methods, or primary suction thrombectomy (Fig. 4).…”
Section: Future Experimentsmentioning
confidence: 99%
“…Further experiments will help to validate and confirm the recalcitrance of our bifurcation model. This includes the evaluation of different established modalities for thrombectomy, such as the ADAPT (A Direct Aspiration First Pass Technique) 17 and ARTS (Aspiration-Retriever Technique for Stroke) 12 methods, or primary suction thrombectomy (Fig. 4).…”
Section: Future Experimentsmentioning
confidence: 99%
“…In Penumbra thrombectomy, an aspiration catheter with a larger profile diameter must be navigated through the convoluted intracranial artery, especially at the carotid siphon. Although, theoretically, navigability of aspiration catheters has improved since the launch of newer versions, 10) larger catheters still confer difficulty during delivery to the intracranial arteries. A larger profile can also often create a gap between the guide four patients (40.0%) with the old aspiration catheter system, eight (80.0%) in the first stent group, and eight (80.0%) in the second stent group, there was no significant difference in the recanalization success rate among these groups (p = 0.122).…”
Section: Discussionmentioning
confidence: 99%
“…A recent trial of the a direct aspiration first pass technique (ADAPT) technique using Penumbra MAX/MAX ACE catheters reported that recanalization rates and clinical outcomes were similar to those achieved using stent retrievers. 10) We first used the standard technique with a separator, which was recommended by the manufacturer. Thereafter, we started using the ADAPT technique.…”
Section: Discussionmentioning
confidence: 99%
“…1) Additionally, high recanalization rates have been reported by the a direct aspiration first pass technique (ADAPT), 7,8) which is a modification of the conventional procedure using the Penumbra system. However, acute occlusion of major intracranial arteries may be caused by embolic lesions that cannot be recanalized by the above devices as well as atherosclerotic lesions and arterial dissection.…”
Section: Discussionmentioning
confidence: 99%